Evolution of bismuth-based metal–organic frameworks for efficient electroreduction of CO2. Issue 34 (18th August 2022) - Li, Lili; Kang, Xinchen; He, Meng; Sheveleva, Alena; Hu, Kui; Xu, Shaojun; Zhou, Yiqi; Chen, Jin; Sapchenko, Sergei; Whitehead, George; Vitorica-Yrezabal, Iñigo J.; Lopez-Odriozola, Laura; et al.
Abstract : The impact of porosity of MOFs on their structural evolution during reaction with electrolyte and their use as pre-catalysts for electrochemical reduction of CO2 provide new insights into the design of new MOFs-derived catalysts. Abstract : Understanding the structural and chemical changes that reactive metal–organic frameworks (MOFs) undergo is crucial for the development of new efficient catalysts for electrochemical reduction of CO2 . Here, we describe three Bi(iii ) materials, MFM-220, MFM-221 and MFM-222, which are constructed from the same ligand (biphenyl-3, 3′, 5, 5′-tetracarboxylic acid) but which show distinct porosity with solvent-accessible voids of 49.6%, 33.6% and 0%, respectively. We report the first study of the impact of porosity of MOFs on their evolution as electrocatalysts. A Faradaic efficiency of 90.4% at −1.1 V vs. RHE (reversible hydrogen electrode) is observed for formate production over an electrode decorated with MFM-220-p, formed from MFM-220 on application of an external potential in the presence of 0.1 M KHCO3 electrolyte. In situ electron paramagnetic resonance spectroscopy confirms the presence of ·COOH radicals as a reaction intermediate, with an observed stable and consistent Faradaic efficiency and current density for production of formate by electrolysis over 5 h. This study emphasises the significant role of porosity of MOFs as they react and evolve during electroreduction of CO2 to generate value-added chemicals.